Pengaruh Green Accounting dan Makroekonomi terhadap Kinerja Keuangan Perusahaan Energi Terbarukan (2022–2024) - Ananda Kusuma; Rialdi Azhar (Jurnal Kendali Akuntansi, 2026)
This study aims to examine and analyze the effect of Green Accounting, Exchange Rate, Inflation, Interest Rate, and Foreign Investment on the Financial Performance of renewable energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. This study uses a quantitative approach with secondary data in the form of panel data. Sample selection was conducted using purposive sampling. Data analysis was performed using multiple linear regression with the assistance of statistical software. The results of the simultaneous statistical test prove that all independent variables jointly have a significant effect on financial performance. However, the partial test results (t-test) found that Green Accounting, Inflation, and Foreign Investment have a positive but insignificant effect on Financial Performance. Exchange Rate and Interest Rate have a negative but insignificant effect on Financial Performance. The conclusion of this study indicates that this partial insignificance is due to industry characteristics that require a transition/time lag for ecological investments and foreign capital inflows to impact profitability. In addition, the resilience of management in implementing integrated risk mitigation, such as long-term Power Purchase Agreements (PPA) and access to green financing, is able to operationally cushion macroeconomic shocks. The implication of this study emphasizes the importance of green financing policy support to accelerate the national energy transition.